2015
DOI: 10.1007/s40618-015-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic neuropathy is not associated with homocysteine, folate, vitamin B12 levels, and MTHFR C677T mutation in type 2 diabetic outpatients taking metformin

Abstract: In conclusion, in these type 2 diabetic outpatients circulating levels of tHcy, folate, and the MTHFR C677T mutation are not associated with DPN, which was predicted by creatinine levels, CHD, and dyslipidemia. Metformin therapy is associated with a mild vitamin B12 level reduction, but not with DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
6
39
0
1
Order By: Relevance
“…Among these factors, current therapies, peripheral neuropathy, reduced vision (caused by peripheral retinopathy and cataracts), hypoglycaemia, decreased muscle performance, diabetic foot, orthostatic hypotension, polyuria and nocturia, causing falls especially at night, reduction of reflexes, stroke, and cognitive impairment may all play an important role [19, 20]. Moreover, diabetes is associated with a delay in the wound healing [21], altered biochemical properties, and a reduction of cell proliferation and of collagen content in bone callus [22].…”
Section: Potential Pathophysiological Basis Of the Increased Fractmentioning
confidence: 99%
“…Among these factors, current therapies, peripheral neuropathy, reduced vision (caused by peripheral retinopathy and cataracts), hypoglycaemia, decreased muscle performance, diabetic foot, orthostatic hypotension, polyuria and nocturia, causing falls especially at night, reduction of reflexes, stroke, and cognitive impairment may all play an important role [19, 20]. Moreover, diabetes is associated with a delay in the wound healing [21], altered biochemical properties, and a reduction of cell proliferation and of collagen content in bone callus [22].…”
Section: Potential Pathophysiological Basis Of the Increased Fractmentioning
confidence: 99%
“…The prevalence of vitamin B12 deficiency was 28.1%; however, there was no association between vitamin B12 deficiency and DPN, and Metformin dose did not confer an increase risk on DPN presence [129]. Similar results were reported by other authors, with controversial results, but without strong evidence that vitamin B12 deficiency influences the presence or severity of peripheral neuropathy [130132]. We recommend supplementation with vitamin B12 in those patients with long-term use of Metformin (≥10 years) or concomitant use of PPI/H2A, and evidence of clinical DPN.…”
Section: Diabetic Polyneuropathymentioning
confidence: 55%
“…A possible reason for this finding may be due to the direct neuroprotective effect of metformin through its glucose-lowering effect and antihyperglycemic-independent, direct anti-neuropathic impact on neurons including inhibition of oxidative stressrelated apoptotic cell death [36,37]. Studies by Ahmed et al in South Africa and Russo et al in Italy [38,39] also found no significant difference in the presence of neuropathy between subjects with normal vitamin B 12 levels and those with vitamin B 12 deficiency. Additionally, though classical B 12 deficiency is associated with clinical symptoms such as anemia and peripheral neuropathy, these symptoms are usually absent in those with only biochemical vitamin B 12 deficiency [33].…”
Section: Discussionmentioning
confidence: 97%